A Brief on Estimating Costs of Intangible Assets During Capital Budgeting Decisions - Jarrett, Jeffrey E. (Advances in Social Sciences Research Journal, 2022)
By examining financial reporting methods to determine the effects of a pandemic, intellectual property rights and other intangible assets. The goal is to explain how these factors are related to capital budgeting decision utilizing a very common and useful model for capital budgeting.